Does a Temporary Increase in Glycosaminoglycan (GAG) Indicate Positive Intervertebral Disc Adaptation? - Horschig, Aaron; Lock, Andrew; Williams, Brogan; Johnson, David (British Journal of Healthcare and Medical Research, 2023)
Many in the scientific community have been debating the extent to which the spine can adapt. While it is widely accepted that vertebral bones can adapt and become stronger/denser with appropriately dosed loading, many unanswered questions remain regarding intervertebral discs (IVDs). Recently, some claim that IVDs can adapt to stress under load and become stronger and more resilient over time based on the findings from a recent study “Imaging of exercise-induced spinal remodeling in elite rowers” by Frenken et al 2022 in the Journal of Science and Medicine in Sport. The Frenken paper investigated the IVD Glycosaminoglycan (GAG) increases in elite rowers over the course of a training period, which was to indicate a positive adaptation to training based on the assumption that GAG is decreased in discs with degeneration. A cause-and-effect relationship does not exist and in fact, is unlikely to exist particularly with a historically high prevalence of disc degeneration in rowers. The Frenken paper supports the notion that the GAG content alters in response to certain stimuli; however, we cannot conclude that a temporary increase in GAG content supports the hypothesis that the IVD adapts positively to load. An alternative postulate is that repetitive biomechanical loading of the intervertebral disc through intra-lumbar flexion (as observed in rowing) does stimulate nutrient transport across the vertebral endplates; however, this biochemical response is of limited benefit and should not be perceived as a positive adaptation to the overall longevity and health of the disc. In this context, the elevation in GAG may be more appropriately interpreted as a maladaptive indicator of undesirable biomechanical intra-lumbar flexion stress that progressively drives cartilaginous endplate sclerosis leading ultimately to the clinically observed accelerated disc degeneration, future back pain symptoms, and reduced GAG concentration in rowers. This contrasting interpretation is consistent with the clinical observation of intra-lumbar flexion biomechanical stress, the transient rise in GAG followed by a reduction that correlates with the radiological findings and back pain symptoms evolving over time in elite rowers.